Worldwide phylogeny and biogeography of Cardamine flexuosa (Brassicaceae) and its relatives - Zozomová Lihová, Judita; Koch, Marcus (American journal of botany, 2006)
Phylogenetic relationships, biogeography, and taxonomy of a group of taxa putatively related to the tetraploid Cardamine flexuosa were explored using sequences of the internal transcribed spacer region of nrDNA (ITS) and the trnL-trnF region of cpDNA. Taxon sampling focused on eastern Asia, North America, and Europe, and included 19 taxa represented by 177 and 182 accessions for each data set, respectively. Our analyses provided unequivocal evidence that Asian weedy populations traditionally assigned to C. flexuosa form an independent evolutionary lineage and represent a distinct taxon from European C. flexuosa. The allopolyploid origin of this common weed in paddy fields, its origin, and/or spread associated with the establishment of suitable man-made habitats are suggested. It is also found as an introduced weed in Australia and North America. Phylogenetic relationships and the associated taxonomic implications are presented and discussed for the group as a whole. Contrasting patterns of genetic variation (particularly in cpDNA) among different species were revealed. While very little haplotype diversity was found in widespread C. hirsuta and C. flexuosa, greater variation, showing phylogeographic structure, was observed in the tetraploid C. scutata within a relatively small area of Japan.